Assessing the Influence of Vegan, Vegetarian and Omnivore Oriented Westernized Dietary Styles on Human Gut Microbiota: A Cross Sectional Study - Losasso, Carmen; Eckert, Ester M.; Mastrorilli, Eleonora; Villiger, Jorg; Mancin, Marzia; Patuzzi, Ilaria; Di Cesare, Andrea; Cibin, Veronica; Barrucci, Federica; Pernthaler, Jakob; Corno, Gianluca; Ricci, Antonia (Frontiers in Microbiology, 2018)
Diet and lifestyle have a strong influence on gut microbiota, which in turn has important implications on a variety of health-related aspects. Despite great advances in the field, it remains unclear to which extent the composition of the gut microbiota is modulated by the intake of animal derived products, compared to a vegetable based diet. Here the specific impact of vegan, vegetarian and omnivore dietary choicesfeeding type on the composition of gut microbiota of 101 adults was investigated among groups homogeneous for variables known to have a role in modulating gut microbial composition such as age, anthropometric variables, ethnicity and geographic area. The results displayed a picture where the three different dietetic profiles could be well distinguished on the basis of participant’s dietetic regimen. Regarding the gut microbiota; vegetarians had a significantly greater richness compared to omnivorous. Moreover, counts of Bacteroidetes related operational taxonomic units were greater in vegans and vegetarians compared to omnivores. Interestingly considering the whole bacterial community composition the three cohorts were unexpectedly similar. , which is probably due to their common intake in terms of nutrients rather than food, e.g. high fat content and reduced protein and carbohydrate intake. This finding suggests that fundamental nutritional choices such as vegan, vegetarian or omnivory do influence the microbiota but do not allow to infer conclusions on gut microbial composition, and suggested the possibility for a preferential impact of other variables, probably related to the general life style on shaping human gut microbial community in spite of dietary influence. Consequently, research were individuals are categorised on the basis of their claimed feeding types is of limited use for scientific studies, since it appears to be oversimplified.